2022
DOI: 10.1093/brain/awac241
|View full text |Cite
|
Sign up to set email alerts
|

Alternative processing of humanHTTmRNA with implications for Huntington’s disease therapeutics

Abstract: Huntington disease is caused by a CAG repeat expansion in exon 1 of the huntingtin gene (HTT) that is translated into a polyglutamine stretch in the huntingtin protein (HTT). We previously showed that HTT mRNA carrying an expanded CAG repeat was incompletely spliced to generate HTT1a, an exon 1 only transcript, which was translated to produce the highly aggregation-prone and pathogenic exon 1 HTT protein. This occurred in all knock-in mouse models of Huntington’s disease and could be detected in patient cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…We have previously shown that in R6/2 mice with 90 CAGs and YAC128 mice, HTT aggregation in the nucleus remained relatively diffuse throughout disease progression. 36,51 We have also previously demonstrated that, in HTTexon1 and knock-in mouse models of Huntington's disease, the steady-state levels of soluble HTT isoforms are cytoplasmic and that HTT fragments remain in the nucleus because they have aggregated into high-molecular weight complexes. 36,42,52 Here, we have shown that HTT aggregation in zQ175 striatal nuclei was present as early as 6 weeks of age, well before transcriptional dysregulation has been reported 49 and consistent with transcriptional dysregulation being caused by aggregated HTT.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that in R6/2 mice with 90 CAGs and YAC128 mice, HTT aggregation in the nucleus remained relatively diffuse throughout disease progression. 36,51 We have also previously demonstrated that, in HTTexon1 and knock-in mouse models of Huntington's disease, the steady-state levels of soluble HTT isoforms are cytoplasmic and that HTT fragments remain in the nucleus because they have aggregated into high-molecular weight complexes. 36,42,52 Here, we have shown that HTT aggregation in zQ175 striatal nuclei was present as early as 6 weeks of age, well before transcriptional dysregulation has been reported 49 and consistent with transcriptional dysregulation being caused by aggregated HTT.…”
Section: Discussionmentioning
confidence: 97%
“…Another interesting issue to examine in the future is alternative transcript variants of both genes, ATXN3 and HTT . In this research, we wanted to focus on the main variants of each transcript, but analyses on, e.g., HTT intron1 variant [ 14 , 42 ] or ATXN3 transcripts which does not contain exon 11 (which lead to the translation of ataxin3-a long and ataxin3-a short proteins) [ 26 ], might be interesting in terms of revealing new facts regarding the pathogenesis of both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of mutant transcripts in pathogenic mechanisms in polyQ diseases is being unraveled [10][11][12][13]. RNA-related studies have demonstrated so far: incomplete splicing of HTT mRNA [14], abnormal interactions of RNAs containing expanded CAG repeats with proteins [15,16], and RNA foci formation [17,18], and potential importance of alternative polyadenylation of various polyQ transcripts [19]. Furthermore, mutant polyQ disease transcripts have been shown to be promising therapeutic targets in strategies that aim to downregulate mutant gene expression [2,9,20].…”
Section: Introductionmentioning
confidence: 99%
“…While preparing this manuscript, another recently published study from the Bates lab recapitulates the data in the present study, further solidifying the potential importance of RNA clusters in HD. 88 Additional work is necessary to delineate and link the molecular mechanisms involved in mHTT mRNA clustering to HD pathology. However, this work provides clear evidence identifying mutant mRNA nuclear aggregation as one of the biomolecular signatures of HD, thus adding HD to a growing list of repeat-associated, neurodegenerative disorders with the demonstrated abnormalities in RNA processing and localization.…”
Section: Discussionmentioning
confidence: 99%